The Teacher, the Scapegoat: Analyzing Hori in the Film Monster - Chertian, Vivian Graciela (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
In society, the clash of different people, values, and interests in desiring a single shared object could cause the accumulation of conflicting forces to be directed at a single innocent individual. When it resulted in the banishment or execution of the blamed individual, it was known as scapegoating. One of the parties implied to be prone to scapegoating in a community, as demonstrated in the film Monster, is teachers. Using the qualitative descriptive method, this paper investigated the scapegoating mechanism in the case of Hori, a teacher character in Monster, through his actions and words when interacting with other characters. Three main parties were involved in the process of scapegoating: a parent, Hori’s colleagues and partner, and the students. The scapegoating started when a student, Minato, accused Hori of conducting verbal and physical abuse. The single parent’s overwhelming concern, the school staff’s priority in protecting the school’s reputation, and the students’ reluctance to be involved in the case caused them to perceive Hori as a threat to each party’s well-being. Despite Hori’s innocence, the accumulation of hostility resulted in Hori’s expulsion from school. The case in the story implied the dominant power that the school community members have against teachers, highlighting the fragility of a teacher’s position in society.